Virtual states of light non-Borromean halo nuclei - Delfino, A.; Frederico, T.; Hussein, M. S.; Tomio, Lauro [UNESP] (American Physical Society (APS), 2000)
It is shown that three-body non-Borromean halo nuclei like [Formula Presented] [Formula Presented] considered as neutron-neutron-core systems, have p-wave virtual states with energy of about 1.7 times the corresponding neutron-core binding energy. We use a renormalizable model that guarantees the general validity of our results in the context of short range interactions. © 2000 The American Physical Society.